Quantification of Nitrosomonas oligotropha and Nitrospira spp. Using Competitive Polymerase Chain Reaction in Bench-Scale Wastewater Treatment Reactors Operating at Different Solids Retention Times - Dionisi, Hebe Monica (2002)
The effect of solids retention time (SRT) on ammonia and nitrite‐oxidizing bacteria was measured by Nitrosomonas oligotropha‐like ammonia monooxygenase A and Nitrospira 16S rDNA competitive polymerase chain reaction assays in a complete‐mix, bench‐scale, activated‐sludge system. During steady‐state operation, nitrification was complete in the 20‐ and 10‐day SRT reactors, nearly complete in the 5‐day SRT reactor, and incomplete in the 2‐day SRT reactor (76% ammonia oxidation and 85% nitrite oxidation). Total microbes, measured by dot‐blot hybridizations, ranged from 3 × 1011 to 3 × 1012 cells/L, and increased with increasing SRTs. The concentration of the ammonia‐oxidizer N. oligotropha dropped 100‐fold from the 20‐day SRT (5 × 109 cells/L) to the 2‐day SRT (≤4 × 107 cells/L). Thus, N. oligotropha became a much smaller fraction of the total biomass in the poorly performing 2‐day SRT reactor. The concentration of Nitrospira cells also decreased (10‐fold) as the SRT was reduced from 20 days to 2 days. However, the number of Nitrospira cells was always greater than the number of N. oligotropha cells measured in each reactor (10‐ to 60‐fold). While Nitrospira comprised 1 to 2% of the biomass, N. oligotropha represented only 0.04 to 0.27% of the total population. This low percentage suggests that N. oligotropha was not a dominant ammonia oxidizer in the bench‐scale systems.